The Association between Fetal Renal Artery Doppler Flow with Hourly Urine Output and Amniotic Fluid Volume of Fetuses with a Gestational Age of 30 to 34 Weeks - Neda Nikpour; Maryam Nurzadeh; Narjes Tavakolikia; Lida Mohammadpour; Mahsa Naemi (Iranian Journal of Neonatology)
Background: The present study investigated the association between fetal renal artery Doppler flow, hourly urine output, and amniotic fluid volume in fetuses with a gestational age of 30 to 34 weeks in normal pregnancies. Methods: This cross-sectional study was conducted on 95 eligible pregnant women referred for their routine third-trimester care from March 2022 to March 2023. Each fetus's amniotic fluid volume, kidney size, and hourly urine output were recorded in resistance (RI) and plausibility (PI) indexes of the umbilical and renal arteries. The hourly urine production was calculated by considering bladder volume differences at a 30-minute duration. Results: With gestational age increasing, amniotic fluid volume (p-value=0.005) and the hourly urine output (p-value=0.005) increased significantly. RI of umbilical (p-value=0.022), right (p-value<0.001), and left (p-value=0.001) renal arteries and PI of right (p-value=0.042) and left (p-value=0.001) renal arteries decreased significantly through the pregnancy. There was a negative linear association between RI and PI of the renal arteries with hourly urine output. The results showed that the mean of renal artery Doppler indices, including right and left RI (0.87 ± 0.08 vs. 0.88 ± 0.07, p-value=0.274) and right and left PI (2.52 ± 0.59 vs. 2.56 ± 0.64, p-value=0.614) was similar in both sides. In adjusted linear regression analysis, two variables of gestational age and renal artery RI were (p-value<0.001) significantly associated with hourly urine output. Conclusion: The fetus's renal artery Doppler findings and urine outputs seem to represent fetal renal function, warning the physicians about post-natal evaluation after birth.